Pulmonary Hypertension In Chronic Renal Failure - Rifa'i, Achmad; Setiadi, Satya (Universitas Brawijaya, 2025)
Chronic kidney disease affects more than 10% of the global population, with prevalence of 14.8% in the USA and 10.8% in Asia. The disease has more prevalence in older age individuals, women, and those with diabetes and high blood pressure, who are also at a higher risk of developing heart disease. Pulmonary hypertension is condition that occurs when the pressure in the pulmonary artery rises more than 20 mm hg. The occurrence rate of the condition is approximately 35% to 38% among hemodialysis patients and 12% to 36% among external peritoneal dialysis patients. Research indicates that a majority of individuals with chronic kidney disease also experience pulmonary hypertension. This is particularly true for individuals undergoing dialysis. The exact etiology of pulmonary hypertension in these individuals especially in ESRD is unknown, but there are numerous factors that can lead to the development of this condition. The writer want to examine the connection between pulmonary hypertension and chronic renal failure, paying particular attention to the underlying pathological mechanisms.